Hofbauer-Buchner eyelet affects circadian photosensitivity and coordinates TIM and PER expression in Drosophila clock neurons. - Veleri, S.; Rieger, D.; Helfrich-Forster, C.; Stanewsky, R. (Journal of Biological Rhythms, 2007)
Extraretinal photoreception is a common input route for light resetting signals into the circadian clock of animals. In Drosophila melanogaster, substantial circadian light inputs are mediated via the blue light photoreceptor CRYPTOCHROME (CRY) expressed in clock neurons within the brain. The current model predicts that, upon light activation, CRY interacts with the clock proteins TIMELESS (TIM) and PERIOD (PER), thereby inducing their degradation, which in turn leads to a resetting of the molecular oscillations within the circadian clock. Here the authors investigate the function of another putative extraretinal circadian photoreceptor, the Hofbauer-Buchner eyelet (H-B eyelet), located between the retina and the medulla in the fly optic lobes. Blocking synaptic transmission between the H-B eyelet and its potential target cells, the ventral circadian pacemaker neurons, impaired the flies' ability to resynchronize their behavior under jet-lag conditions in the context of nonfunctional retinal photoreception and a mutation in the CRY-encoding gene. The same manipulation also affected synchronized expression of the clock proteins TIM and PER in different subsets of the clock neurons. This shows that synaptic communication between the H-B eyelet and clock neurons contributes to synchronization of molecular and behavioral rhythms and confirms that the H-B eyelet functions as a circadian photoreceptor. Blockage of synaptic transmission from the H-B eyelet in the presence of functional compound eyes and the absence of CRY also results in increased numbers of flies that are unable to synchronize to extreme photoperiods, supplying independent proof for the role of the H-B eyelet as a circadian photoreceptor.